Toward Understanding the Experience of Upper Egyptian Female Domestic Workers Internally Migrating to Cairo - Hamad, Aliaa (AUC Knowledge Fountain, 2025)
Abstract This thesis examined the journeys of a group of female Egyptian domestic workers who had internally migrated from their respective rural communities in Upper Egypt to Cairo. It employed a rapid ethnographic design to attempt to better understand their migration experience. By investigating what prompted them to migrate and their agency in how they networked and what social remittances they transmitted, it aimed to empower this group of women by giving them a voice to share their narratives and help them become more cognizant of their identity and agency as they reflect on their respective journeys (Reinhartz & Chase, 2002).